A blockchain-based Roadside Unit-assisted authentication and key agreement protocol for Internet of Vehicles - Xu, Zisang; Liang, Wei; Li, Kuan-Ching; Xu, Jianbo; Jin, Hai (Journal of parallel and distributed computing, 2021)
A fundamental layer of smart cities, the Internet of Vehicles (IoV) can significantly improve transportation efficiency, reduce energy consumption, and traffic accidents. However, because of the vehicle and the RoadSide Units (RSU) use wireless channels for communication, the risk of information being leaked or tampered is highly increased. Therefore, secure and reliable authentication and key agreement protocol is the masterpiece of IoV security. As most of the existing authentication protocols pertain to a centralized structure and single Trusted Authority (TA) network model, all vehicles involved can only perform mutual authentication with one TA through the intermediate node RSU, and thus, the efficiency of these centralized authentication protocols is easily affected by TA’s communication and computing resource bottlenecks. In this article, a blockchain-based authentication and key agreement protocol is designed for the multi-TA network model, moving the computing load of TA down to the RSU to improve the efficiency of authentication. In addition, blockchain technology is used for multiple TAs to manage the ledger that stores vehicle-related information, which results in vehicles that can easily achieve cross-TA authentication. Both formal and informal security analysis and simulation results from ProVerif show that the proposed protocol is secure. Comparisons with other existing work show that the proposed protocol has less computational overhead, higher authentication efficiency, and can resist various common attacks. •Adopt multi-server model and solve cross-server authentication based on blockchain.•Move computing load down to roadside unit to reduce bottlenecks of trusted authority.•Only a limited number of lightweight cryptographic tools are used.